Pressureless sintering of Al2O3/Ni nanocomposites produced by heterogeneous precipitation method with varying nickel contents. (June 2016) - Kafkaslıoğlu, Betül; Tür, Yahya Kemal
Abstract: Al2 O3 /Ni nanocomposites with varying Ni contents (1, 3, 5 vol.%) were produced by pressureless sintering of Al2 O3 and nano Ni powder mixture, prepared by a heterogeneous precipitation method. Better densification was achieved by increasing the sintering temperature and decreasing the Ni content. The highest density was obtained from the samples with 1 vol.% Ni content sintered at 1550 °C. X-ray diffraction analysis was used in order to verify the Ni particle formation in the sintered specimens. SEM analyses were conducted on the polished and thermally etched specimens and Al2 O3 grain and Ni metal particle sizes were measured. It was observed that Ni particles were dispersed homogeneously in the alumina matrix and they were commonly located at the grain boundaries or at the triple junctions. Vickers hardness of the specimens was measured to investigate the hardness-material relationship which was strongly dependent on microstructure which is affected by the sintering temperature and Ni content. Highlights: Pressureless sintering was shown as an effective method to densify the nanocomposites that contain low metal ratio. Heterogeneous precipitation provided relatively small and varying metal particle sizes even at 1550°C. Through Ni particles increased hardness by Hall-Petch effect and through high densification, hardness could be maintained.